2001
DOI: 10.1677/joe.0.1710183
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of uptake and compartmentalization of 3,5,3'-tri-iodothyronine in cultured neonatal rat cardiomyocytes

Abstract: The uptake of tri-iodothyronine (T 3 ) in cultured neonatal rat cardiomyocytes was investigated and compared with the uptake of reverse T 3 (rT 3 ) and thyroxine (T 4 ). Cellular compartmentalization of T 3 was studied by distinguishing T 3 activity associated with the plasma membrane from that in the cytosol or incorporated in the cell nucleus. T 3 and T 4 uptake displayed similar temperature dependencies which, in magnitude, differed from that of rT 3 uptake. T 3 uptake was Na + independent, and sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Initially, no saturable T4 uptake was observed in rat cardiomyocytes, but subsequent studies indicated the presence of low-affinity (Km in mM range) transporter(s) shared by T3 and T4 in primary rat cardiomyocytes as well as in the H9c2 embryonic heart cell line. T4 and T3 uptake in these cells is Na + independent and partially inhibited by Trp, suggesting that is mediated in part by a T-type amino acid transporter [32,33].…”
Section: Cellular Uptake Of Thyroid Hormonementioning
confidence: 90%
See 1 more Smart Citation
“…Initially, no saturable T4 uptake was observed in rat cardiomyocytes, but subsequent studies indicated the presence of low-affinity (Km in mM range) transporter(s) shared by T3 and T4 in primary rat cardiomyocytes as well as in the H9c2 embryonic heart cell line. T4 and T3 uptake in these cells is Na + independent and partially inhibited by Trp, suggesting that is mediated in part by a T-type amino acid transporter [32,33].…”
Section: Cellular Uptake Of Thyroid Hormonementioning
confidence: 90%
“…Finally, carrier-mediated transport has also been reported for T3 in rat neonatal cardiomyocytes in primary culture [31,32]. Initially, no saturable T4 uptake was observed in rat cardiomyocytes, but subsequent studies indicated the presence of low-affinity (Km in mM range) transporter(s) shared by T3 and T4 in primary rat cardiomyocytes as well as in the H9c2 embryonic heart cell line.…”
Section: Cellular Uptake Of Thyroid Hormonementioning
confidence: 91%